PELAKSANAAN PROGRAM KAMPUS MENGAJAR ANGKATAN IV DI SD NEGERI 163 TELLULIMPOE KABUPATEN WAJO - Andi Nirwana; Sri Wahyuni Mumang (Jurusan Pendidikan Guru Sekolah Dasar Kampus VI Bone, 2024)
The Class IV Teaching Campus Program from the Ministry of Education and Culture of the Republic of Indonesia provides opportunities for students to broaden their horizons and gain experience in supporting the teaching and learning process in elementary schools. This service activity was carried out at SD Negeri 163 Tellulimpoe, Wajo Regency, and the object of research was the implementation of the Teaching Campus program at the school. Data collection methods include observation, interviews, and documentation. This program includes implementing teaching and learning activities, introducing learning technology to teachers, as well as assisting teachers in providing and completing learning administration